Control químico de araña roja Tetranichus urticae Koch 1836 en el cultivo de pepino Cucumis sativus - Cerezo Vera, Segundo Milton (2022)
Cucumber cultivation is one of the vegetables that is growing due to the large items that can be obtained from it, as long as it is given good technical management, but on certain occasions it can be affected by various factors, including which we can mention, environmental conditions, use of seed, nutrition, irrigation among others. The present investigation called Chemical control of red spider Tetranichus urticae Koch 1836 in the cultivation of cucumber Cucumis sativus, had as general objectives to identify the main chemicals that are used for the management of red spider Tetranichus urticae in the cultivation of cucumber Cucumis sativus and specific to describe the main damages caused by the red spider urticae in the cultivation of cucumber sativus and to know the active ingredients and correct chemical dosages for the management of the spider mite Tetranichus urticae in the cultivation of cucumber sativus. Based on the evidenced findings, it was possible to observe that among the main damages caused by the red spider, damage to the cucumber leaves is found, causing yellowing of the same and a blackish coloration is produced in the fruit, the main products used for Its management includes bifenazate, oberon, galil, acetameprid and desnukador.